2016
DOI: 10.1590/18069657rbcs20150099
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crops Effects on Soil Chemical Properties and Onion Yield

Abstract: ABSTRACT:Cover crops contribute to nutrient cycling and may improve soil chemical properties and, consequently, increase crop yield. The aim of this study was to evaluate cover crop residue decomposition and nutrient release, and the effects of these plants on soil chemical properties and on onion (Allium cepa L.) yield in a no-tillage system. The experiment was carried out in an Inceptisol in southern Brazil, where cover crops were sown in April 2012 and 2013. In July 2013, shoots of weeds (WD), black oats (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 27 publications
4
45
0
4
Order By: Relevance
“…This is because most of the P in plant tissue is found in inorganic forms (Casali et al, 2011;Marschner, 2012) and the inorganic P in the tissue makes up the labile compartment. These results corroborate with those obtained by Fernandes et al (2000), Pereira et al (2008), Casali et al (2011), and Oliveira et al (2016), who noticed that most of the tissue P is found in the soluble inorganic form in well-nourished plants grown in soil with sufficient nutrient content.…”
Section: Distribution Of P Forms In Cover Crop Residuessupporting
confidence: 92%
See 2 more Smart Citations
“…This is because most of the P in plant tissue is found in inorganic forms (Casali et al, 2011;Marschner, 2012) and the inorganic P in the tissue makes up the labile compartment. These results corroborate with those obtained by Fernandes et al (2000), Pereira et al (2008), Casali et al (2011), and Oliveira et al (2016), who noticed that most of the tissue P is found in the soluble inorganic form in well-nourished plants grown in soil with sufficient nutrient content.…”
Section: Distribution Of P Forms In Cover Crop Residuessupporting
confidence: 92%
“…This is due to the difference in accumulation of P forms in the tissue. It indicates that the P release rate depends not only on total content in the tissues (Oliveira et al, 2016), but also on how P is stored, in addition to other characteristics of the residue, such as C/N ratio (Tables 1 and 4) and leaching of water-soluble compounds degraded by the microbial population of plant residues (Ferreira et al, 2014). According to Aita and Giacomini (2003), this is because most microorganisms, especially fungi and bacteria, which colonize plant residues and part of total soil organic C, are used during decomposition as a source of ATP and are in part released into the atmosphere in the form of CO 2 (Manzoni et al, 2008).…”
Section: Mineralization Of Cover Crop P Formsmentioning
confidence: 98%
See 1 more Smart Citation
“…The low POC value found in the surface soil layer (0-5 cm) of plots with oilseed radish may be due to the lower lignin and higher cellulose content of this species compared to the other cover plants (Oliveira et al, 2016). Consequently, they decompose more quickly and result in lower soil POC content.…”
Section: Resultsmentioning
confidence: 92%
“…Intercropping black oats with oilseed radish, which has an axial root and a deep root system, promotes physical and chemical effects in depth. The combination favors soil aggregation as well as carbon increase and protection in aggregates, in this case POC, since this fraction is directly related to plant material recently added to the soil (Loss et al, 2015;Wick et al, 2014;Oliveira et al, 2016).…”
Section: Resultsmentioning
confidence: 99%